A.N. Vylegzanin, V.K. Zilanov. Spitsbergen: legal regime of adjacent marine areas. Edited and translated by W.E. Batler. Eleven international publishing. 2007. XVII, 167 pp. - G. M. Melkov (Moscow Journal of International Law, 2007)
The competition between States over natural resources of the continental shelf of Spitsbergen and its superjacent waters increases dramatically nowadays. The authors clearly show that the contemporary disagreements of Norway with Russia and with Iceland and Spain over Norway’s expanse of powers on Spitsbergen are “early manifestations of an imminent legal arena with regard to the oil and gas reserves of shelf areas surrounding Spitsbergen”. As has been written by A.G. Granberg, Member of the Presidium of Russian Academy of Sciences, Chairman of the Council for the Study of Productive Forces, in the preface to the book, “all that happens in the Arctic affects the interests of Russia”. In his Introduction William E. Butler, English editor and translator of the book, emphasize that “Russian international legal perceptions of the legal status of Spitsbergen itself and the adjacent marine areas are little-known abroad. The present monograph is the first substantial elaboration of Russian doctrinal views on the subject for many decades and certainly the first ever to be made accessible in the English language”. The book provides an analysis of the legal regime of Spitsbergen based on the sound scholarly research. The individual chapters reveal the legal history and the core instruments of the regime. The issues discussed include legal status of Spitsbergen prior to 1872, Russo-Swedish/Norwegian Agreement of 1872, international conferences concerning Spitsbergen (1910-1914), Paris conference (1919-1920) and Russia, Treaty of Spitsbergen (1920), Norwegian regulation beyond the territorial waters of Spitsbergen, international law and Norwegian preservation of bioresearches around Spitsbergen, Russo-Norwegian treaties as basis for ecosystem management of natural resources of the Barents sea. As A.G. Granberg has noted, “the value of this work lies in its scrupulousness legal precision, and persuasiveness based on documents”.